PELATIHAN BUDIDAYA DAN PENANAMAN PALA (Myristica fragrans Houtt ) MENINGKATKAN KAPASITAS PETANI PALA DI DESA WATUI - KABUPATEN SERAM BAGIAN BARAT - Siahaya, Troice E.; Pietersz, Juglans H.; Silaya, Thomas M.; Boreel, Aryanto; Amanukuany, Meidhy A.; Latupeirissa, Yeri A. (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this Community Service activity is: Equipping the Community Around the Forest (Watui Village) with knowledge and skills in forest management Clarifying the territorial area of ​​Watui Village by Planting Long-lived. This Community Service activity was carried out in Watui Village, Elpaputih District, West Seram Regency. In July - November 2024. The method used was the socialization and demonstration method. The results of the study showed that the Implementation of Phase I; Observation and Coordination, it was known that there was a lack of community knowledge regarding planting patterns and knowledge of male and female nutmeg types. Through coordination with village officials, it was discovered that there was a community conflict that had occurred because there were differences in perception and low understanding of the community. Phase II, counseling and training The community seemed enthusiastic in the discussion as seen from the active question and answer session. Proper nutmeg seed cultivation is one of the keys to success in obtaining quality plant seeds. Nutmeg seeds selected as seeds must meet physical, physiological, and genetic quality requirements. Implementation of Phase III. Monitoring and Evaluation, Evaluation results show that farmers can accept the material and have been able to apply what they have learned in the training. In practice, farmers create two small groups that carry out a series of stages according to the training they received previously. From the 350 seed sowing trials carried out, 257 seeds were successfully germinated (73.42%).